Optimalisasi Pembelajaran Pendidikan Agama Hindu Menggunakan Media Pembelajaran Berbasis Digital - I Gede Dharman Gunawan; Putu Wisnu Saputra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
During the Covid-19 pandemic, it still has an impact on the world of education, educators are more required to carry out various kinds of innovations by utilizing digital-based learning media in learning, especially Hindu religious education learning. Learning media that are successful in learning Hindu religious education can change the behavior of students (behavior change), improve student learning outcomes, and the learning process becomes more optimal. The successful use of digital-based learning media cannot be separated from how well the media is planned. One of them is the use of google classrooms and social media as learning media by paying attention to various aspects such as the objectives, condition of students, supporting facilities, available time, and the ability of teachers to use them appropriately according to the characteristics of Hindu religious education subjects. Keywords: Hindu Religion Learning, Digital Learning Media